First Principles Study of Penta-siligraphene as High-Performance Anode Material for Li-Ion Batteries - Hewen Wang; Musheng Wu; Zhengfang Tian; Bo Xu; Chuying Ouyang (Nanoscale Research Letters, 2019)
Abstract From first principles calculations, a novel pentagonal Si/C complexity is predicted to have potential applications as a promising anode material for Li-ion batteries. It is found that the structural and thermal stability of the penta-siligraphene (P-Si2C4) is better than penta-graphene that is composed of C atoms only. Electronic band structure analysis shows that the empty C-2p z state in the P-Si2C4 provides space to accommodate and stabilize electrons from Li, which makes Li storage energetically favorable. As a result, four Li atoms can be stored by one formula unit of the P-Si2C4, corresponding to a theoretical gravimetric Li storage capacity of 1028.7 mAhg−1. The metallic electronic structures of the Li-adsorbed P-Li x Si2C4 as well as very small Li migration energy barriers are beneficial for fast charge/discharge performance of the battery. The mechanism on the Li adsorption interaction on the P-Si2C4 is discussed. These results demonstrate a novel strategy to design two-dimensional Si/C complex anode materials for high-performance Li-ion batteries.